Numerical and experimental analysis of mechanical and fatigue properties of special shaped 3D printed sample (Fracture and Structural Integrity, 2025)
Research in the field of property analysis of 3D printed structural elements raises many new questions. A major challenge is to understand the behavior of the material, as the raw material and the resulting printed sample cannot be considered the same in this respect. In 3D printing, the properties of the sample change due to high temperatures, changes in the state of the raw material and different setups. Currently, there is no standard for determining certain properties, which leads to the need for appropriate use of experimental and numerical tools. This study highlights the results of tensile testing and numerical analysis of a special 3D printed shape. Different material settings were used to allow a complete inverse analysis of the specimen behavior and calibration between experiment and model. The model was created in Ansys software and was prepared in several variations to be as close as possible to the real specimen. Subsequently, the numerical model was subjected to a simplified fatigue analysis with respect to the S-N curves and the predicted fatigue life of the specimen was determined.
Keywords: Numerical modeling; shear; 3D printing; experiment; fatigue